Fire Hazard Risk Assessment Due to Domino Effect in Petroleum Plant - Suresh Naidu, Shaarvin Naidu (IRC, 2021)
Fundamentally, this project would be on modelling of implementation on multiple risk methods to study and investigate the most reliable methods has not been well investigated for domino fire spread specifically in the facilities of petroleum industries.